Estudo de migração ao ambiente de contratação livre de energia, utilizando o método de Florezi - Paulo, João Rafael (2020)
With the considerable increase in the physical structure of UTFPR, linked to the institution consumption cost, as an example the electric energy, a study was needed on cost saving methods. The object of this paper is conduct a study of UTFPR current energy contracting environment and verify the viability of migrating to the free contracting environment. With this, it is intended to raise the profile of current electricity consumption and check if this is the best mode of tariff contraction. Finally, observing by Florezi's method if the migration to the free contracting environment becomes advantageous.